NANOFORMULATIONS OF PAZOPANIB, COMPOSITIONS COMPRISING THE SAME AND METHODS OF TREATING OSTEOARTHRITIS - LIU, YING; SAMPEN, HEE-JEONG IM (2022)
Disclosed herein are nanoparticles comprising Pazopanib or a derivative thereof encapsulated by the copolymer poly(lactic-co-gly colic acid) (PLGA). Also disclosed herein are methods for treating osteoarthritis, inhibiting or preventing cartilage degeneration, and reducing or inhibiting pain-associated depression in subjects with joint pain with nanoparticles comprising Pazopanib or a derivative thereof. Sont divulguées des nanoparticules comprenant du Pazopanib ou un dérivé de celui-ci encapsulé par le copolymère acide poly(lactique-co-glycolique) (PLGA). Sont également divulguées des méthodes de traitement de l'arthrose, d'inhibition ou de prévention de la dégénérescence du cartilage, et de réduction ou d'inhibition de la dépression associée à la douleur chez des sujets atteints de douleur articulaire avec des nanoparticules comprenant du Pazopanib ou un dérivé de celui-ci.